The Problem of Differentiation of Category and Genre - JRBASHYAN, ASHKHEN (Bulletin of Yerevan University B: Philology, 2021)
The article touches upon the evolution of the issue of differentiating literary category and literary genre from antiquity to modern literary theories in literary criticism. Being primarily a means of differentiating modulations in narration in the periodof romanticism the triad of the genre got an absolutely new interpretation. Antique and classicism theories were mainly normative and based upon the formation and composition of rules of the genre. Beginning from romanticism they became hierarchic theories. In the second half of XX century, structuralist theories, resting upon different principles and trying to create a whole and not a monochromatic model, became more active.
Keywords: literary category, literary genre, genre hierarchy, genre denomination, archgenre, modulation, discourse,epism, lyricism, drama